Pregnancy after 35 (Bangladesh Journal of Medical Science, 2015)
Advanced maternal age is associated with certain pregnancy-related risks. Being at risk causes anxiety and concern, which older pregnant women try to ease by being as well-informed as possible. This may be overwhelming to some women due to the large amount of information available. It is important for healthcare providers to be aware of the different feelings and experiences of older pregnant women in order to meet their individual needs within the maternity services.Bangladesh Journal of Medical Science Vol.14(3) 2015 p. 228-235